(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
Za’ba, or his real name Zainal Abidin bin Ahmad is not just a preacher and thinker who has sharp eyes, but also a spiritual teacher. It is based on the idea that emphasizes its meaning, purpose and value of life, which should belong to every human being, especially to a Malay Muslim. Her contributions to the community is unbeatable. It underlines the general appreciation of Islam by emphasizing a determination to use the world for the happiness of life, here and in the hereafter. For Za’ba, mistakes in thinking lead to weaknesses in making a decision and followed by a bad action. Za’ba’s thinking goes beyond times. His writings are almost 70 years old, was found in Qalam magazine which was published in 1952, but the essence and the topics of discussion are still fresh and still relevant until today. The determination of the mindset to ensure that the Malays are on the right track again, as it was recommended in Islam is very evident in his writing. Therefore, this work aims to examine and analyze Za’ba’s spiritual values found in his mind through his writings. Keywords: Za’ba, spirituality, thought, Malay, meaning and value in life